Physiological characterization of ocular melanosis‐affected canine melanocytes. (27th April 2018) - Dawson‐Baglien, Ethan M.; Noland, Erica L.; Sledge, Dodd G.; Kiupel, Matti; Petersen‐Jones, Simon M.
Abstract: Objective: Cairn terriers with ocular melanosis (OM) accumulate large, heavily pigmented melanocytes in the anterior uvea. Darkly pigmented plaques develop within the sclera, leading us to hypothesize that OM uveal melanocytes may have an abnormal migratory capacity. Animals studied: Globes from OM‐affected Cairn terriers and unaffected control eyes enucleated for reasons unrelated to this study were used for immunohistochemistry and to culture melanocytes for in vitro cell behavior assays. Procedures: The scleral plaques of six dogs were immunolabeled for HMB‐45, MelanA, PNL2, CD18, CD204, and Iba‐1 and compared with the pigment cells accumulated within the irides. Cultured uveal melanocytes from OM‐affected and control dogs were compared using conventional assays measuring cell proliferation, invasion capability, and melanin production. Results: Melanocytes isolated from OM eyes had significantly elevated levels of per‐cell melanin content and production compared to controls. The majority of pigmented cells in the scleral plaques were HMB45 positive indicating a melanocytic origin. Many were also CD18 positive. No differences were observed between cultured melanocytes from OM‐affected and control uvea for standard in vitro proliferation or invasion assays. Conclusion: Pigmented cells which accumulate in the sclera of OM‐affected Cairn terriers are predominantly melanocytes; however, in vitro assays of uveal melanocytes did not reveal differences in migratory behavior between OM and control cells. Migratory behavior of OM‐melanocytes may be environment‐dependent. We suggest that RNA sequencing and differential expression analysis would be a useful next step in understanding this disease.